Central Bank Policy and Commercial Banks Distress Level in Nigeria - Princewill Ihenacho Wachukwu; Marshal Iwedi; Sirah Patience Barisua (Journal of Business & Management, 2023)
This study investigated the impact of central bank policy on commercial bank distress Level in Nigeria. Financial time series data were obtained from the central bank of Nigeria statistical bulletin. The data collected were tested using the vector auto regression analysis. The study established that 99.3 percent variation in commercial bank distress level in Nigeria is accounted for by the combined efforts of the explanatory variables of the study. The study concludes that Central Bank of Nigeria must continuously monitor the level of liquidity in order to mitigate any adverse impact on the stability of the financial system.